PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PPKN UNTUK SISWA TUNAGRAHITA DENGAN KONSEP GAMIFIKASI - Pradnyana, I Ketut Andika; Pradnyana, I Made Ardwi; Suyasa, P Wayan Arta (Universitas Pendidikan Ganesha, 2020)
The use of manual instructional media, as well as the limitations of mentally retarded students in comprehending abstract learning material cause a difficulty for teacher to deliver the material. This is necessary for the development of interactive learning media with gamification concept to in teaching PPKn (Civic Education). This study is aimed at designing, implementing, and determining the media feasibility level and students’ responses to the development of interactive learning media for PPKn subject. The development of interactive learning media with gamification concept used the development method of Multimedia Development Life Cycle (MDLC) that consists of 6 development stages, namely: 1. Concept; 2. Design; 3. Material Colleting; 4. Assembly; 5. Testing; and 6. Distribution. The research and development were conducted through the stages of testing beta and alpha to determine the feasibility and students’ responses towards PPKn interactive learning media with gamification concept. The assessment results on material feasibility level were 1.00 and the media were 1.00 with a very decent category. The average response of individual test students was 93,33%, the small group test was 92,22%, and the field test was 91,00%. Interactive learning media with gamification concept was used as teacher’s guideline in providing learning material, so that it could increase children’s concentration and focus. It was shown from the results of students’ responses converted to responses table that students wre categorized as excellent category